Cross-talk between the microbiome and chronic inflammation in esophageal cancer: potential driver of oncogenesis - Tarang Sharma (14150952) (2022)
Esophageal cancer (EC) is frequently considered a lethal malignancy and is often identified at a later stage. It is one of the major causes of cancer-related deaths globally. The conventional treatment methods like chemotherapy, radiotherapy, and surgery offer limited efficacy and poor clinical outcome with a less than 25% 5-year survival rate. The poor prognosis of EC persists despite the growth in the development of diagnostic and therapeutic modalities to treat EC. This underlines the need to elucidate the complex molecular mechanisms that drive esophageal oncogenesis. Apart from the role of the tumor microenvironment and its structural and cellular components in tumorigenesis, mounting evidence points towards the involvement of the esophageal microbiome, inflammation, and their cross-talk in promoting esophageal cancer. The current review summarizes recent research that delineates the underlying molecular mechanisms by which the microbiota and inflammation promote the pathophysiology of esophageal cancer, thus unraveling targets for potential therapeutic intervention. Other Information Published in: Cancer and Metastasis Reviews License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s10555-022-10026-6